Healthcare Innovation—The Epital: An Ethnographic Study of a Unique Way of Organizing Healthcare Innovation - Hesseldal, Louise; Kayser, Lars (Qualitative Sociology Review, 2016)
There is an ongoing debate about how best to organize healthcare innovation. This article introduces and illustrates an alternative way of doing so by studying an emerging informal and inter-organizational network (IION) in practice. Taking an ethnographic research approach, the authors propose the concept of a potluck feast to de-scribe the nature of an IION and the dynamics within it. The relationship between the project and the actors is explored by introducing Steven Brown’s reading of Michel Serres’ concept of the parasite. The unique way of organizing healthcare innovation studied in the article involves an open, sharing approach, where everyone makes themselves an open resource for the project and where the contribution is determined by the actors’ own motivation rather than regulated by a formal setup and contracts. The article argues that the ethnographic research approach is useful to explore the emergence and dynamics of IIONs. In this way, this article contributes to the field of healthcare innovation and how to organize it, and may inspire those who are already in or intend to study this field.